Associations between parent-reported and objectively measured sleep duration and timing in infants at age 6 months. Issue 4 (24th October 2020) - Quante, Mirja; Hong, Benjamin; von Ash, Tayla; Yu, Xinting; Kaplan, Emily R; Rueschman, Michael; Jackson, Chandra L; Haneuse, Sebastien; Davison, Kirsten; Taveras, Elsie M; Redline, Susan
Abstract: Study Objectives: To compare the estimates of sleep duration and timing from survey, diary, and actigraphy in infants at age 6 months, overall and by select demographics and other factors. Methods: In total, 314 infants participating in the Rise & SHINE (Sleep Health in Infancy & Early Childhood study) cohort in Boston, MA, USA, wore an actigraph on their left ankle for 7 days. Parents concurrently completed a sleep diary and the expanded version of the Brief Infant Sleep Questionnaire. Concordance between parent-reported and objective sleep estimates was assessed using Bland–Altman plots, Spearman's rank correlations, intraclass correlations, and linear regression models. Results: Mean infant age was 6.4 (0.6 SD ) months; 51% were female and 42% were Non-Hispanic white. Mean total sleep duration using actigraphy was 526 (67 SD ) minutes per night, 143 (42 SD ) minutes per day, and 460 (100 SD ) minutes during the longest nighttime sleep period. Relative to actigraphy, parent-completed survey and diary overestimated total day (by 29 and 31 minutes, respectively) and night sleep duration (67 and 43 minutes, respectively) and underestimated the longest sleep (58 minutes), with the highest agreement for sleep onset and offset timing (differences < 30 minutes). There was a tendency toward greater bias among short- and long-sleeping infants. Self-reporting bias for diary-measured longest nighttime sleep and total night sleep duration was higher in infants of parents reporting a problem with their baby's night awakenings and in low-income families, respectively. Conclusions: Our findings underscore the need to be cautious when comparing findings across studies using different sleep assessment methods.